An Injury to One Is an Injury to All: Terrorism's Spillover Effects on Bilateral Trade - Cong S. Pham; Chris Doucouliagos (Institute of Labor Economics (IZA), 2017)
In this paper we investigate whether the effects of terrorism in one country spillover to affect trade in neighboring nations. Using a sample of more than 160 countries from 1976 to 2014, we report robust evidence that terrorist attacks in a nation's contiguous neighbors significantly reduce bilateral trade. Each additional terrorist attack in a neighboring country reduces bilateral trade by nearly 0.013% on average, which translates into a reduction of about 6.4 million USD in total trade. Trade effects from terrorist incidents are higher in sub-Sahara. Adverse trade effects hold for different flow and stock measures of terrorism, and even for terrorist incidents with zero casualties. Spillovers from terrorism are relatively long-lived, depressing bilateral trade up to five years after a terrorist event. Our findings are consistent with terrorism adversely impacting bilateral trade through several channels: psychological distress, higher trade costs arising from increased trade insecurity and regulatory burden, and adverse effects on income and trade reform.
Keywords: F14; D74; H56; 330; terrorism; spillovers; bilateral trade